2021
DOI: 10.1111/pan.14281
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for anesthetic‐related complications in pediatric patients with a newly diagnosed mediastinal mass

Abstract: Background: Pediatric patients with a mediastinal mass can experience severe complications while undergoing anesthesia. Nearly, all published reviews involve either patients with an anterior mediastinal mass or patients with an oncologic disease. Aim:The identification of risk factors for anesthetic-related complications in pediatric patients with any type of mediastinal mass. Methods:From January 1, 2008 to December 31, 2019, patients with a newly diagnosed mediastinal mass that underwent anesthesia were retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Pathologically, cerebral palsy is highly associated with the presence of white matter injury (WMI) on ultrasonography, with or without intraventricular hemorrhage. Although rates of cystic WMI have gradually fallen [22], cystic WMI remains highly associated with cerebral palsy [22, 23]. For example, a recent cohort study of 889 survivors of extremely preterm birth at 10 years of age found an odds ratio of 14.3 for cerebral palsy with WMI [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathologically, cerebral palsy is highly associated with the presence of white matter injury (WMI) on ultrasonography, with or without intraventricular hemorrhage. Although rates of cystic WMI have gradually fallen [22], cystic WMI remains highly associated with cerebral palsy [22, 23]. For example, a recent cohort study of 889 survivors of extremely preterm birth at 10 years of age found an odds ratio of 14.3 for cerebral palsy with WMI [23].…”
Section: Introductionmentioning
confidence: 99%
“…Although rates of cystic WMI have gradually fallen [22], cystic WMI remains highly associated with cerebral palsy [22, 23]. For example, a recent cohort study of 889 survivors of extremely preterm birth at 10 years of age found an odds ratio of 14.3 for cerebral palsy with WMI [23]. The characteristic appearance includes cerebral echolucencies consistent with cysts and enlargement of the ventricles.…”
Section: Introductionmentioning
confidence: 99%